Exploration of Waria Jargon in The Movie “Lovely Man” as Representation - Fauzi, Aziz; Prima Sintasari, Diardana; Fajrin, Verawati; Sudarmaji, Imam (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Social life always forms such diverse activities, it is because community groups form the same consciousness as several people so that they form social groups. This research will discuss the variations of language used by the transvestite group in the movie